Real-Time Optimal Scheduling of Multi-Microgrids Considering Renewable Energy Intermittency - Fu, Zongqiang; Li, Bin; Wang, Honglei (Frontiers in Energy Research, 2022)
At present, improving the penetration of renewable energy in energy consumption is an important method to accelerate the realization of peaking CO2 emissions and carbon neutrality. Since multi-microgrid (MMG) can effectively alleviate the impact of intermittence and fluctuation of renewable energy on real-time scheduling, MMG has become an important measure to integrate renewable energy in the distribution network. However, extreme weather and natural disasters can easily cause fault shutdown of wind turbines (WT) and photovoltaics (PV) in the microgrid (MG). To better balance the flexible load removal and satisfaction of MMG, this paper proposes a coordinated scheduling model of MMG covering WT, PV, fuel cell (FC), energy storage system (ESS), and flexible load removal. First, the energy management system (EMS) of MMG collects the information of all the distributed generators’ output and three types of loads, and the contribution bargaining method is applied to realize the energy transaction among all the MGs. Second, two objective functions of maximizing the satisfaction of MMG and maximizing the MG profit, and the scheduling strategy of each MG are formulated. Also, a novel optimization method is applied to solve the amount of flexible load removal of each MG and realize the reasonable scheduling of MMG in the fault state. The superiority of the model and the proposed method have been verified based on a case study